2020
DOI: 10.3390/jcm9010285
|View full text |Cite
|
Sign up to set email alerts
|

Performance of FRAX in Predicting Fractures in US Postmenopausal Women with Varied Race and Genetic Profiles

Abstract: Background: Whether the Fracture Risk Assessment Tool (FRAX) performed differently in estimating the 10-year fracture probability in women of different genetic profiling and race remained unclear. Methods: The genomic data in the Women’s Health Initiative (WHI) study was analyzed (n = 23,981). The genetic risk score (GRS) was calculated from 14 fracture-associated single nucleotide polymorphisms (SNPs) for each participant. FRAX without bone mineral density (BMD) was used to estimate fracture probability. Resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
12
0
2
Order By: Relevance
“…Results were similar in sensitivity analyses excluding data from women who initiated osteoporosis medication therapy during follow-up. We cannot compare the current results regarding discrimination of FRAX and OST for MOF with those of previously published studies because, to our knowledge, studies that examined FRAX in US study cohorts did not evaluate discrimination of FRAX for MOF according to race and ethnicity …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Results were similar in sensitivity analyses excluding data from women who initiated osteoporosis medication therapy during follow-up. We cannot compare the current results regarding discrimination of FRAX and OST for MOF with those of previously published studies because, to our knowledge, studies that examined FRAX in US study cohorts did not evaluate discrimination of FRAX for MOF according to race and ethnicity …”
Section: Discussionmentioning
confidence: 89%
“…We cannot compare the current results regarding discrimination of FRAX and OST for MOF with those of previously published studies because, to our knowledge, studies that examined FRAX in US study cohorts did not evaluate discrimination of FRAX for MOF according to race and ethnicity. [20][21][22][23][24][25][26] Calibration values quantify how well FRAX estimates of 10-year fracture probability match the actual observed 10-year cumulative probability of that fracture outcome. A systematic review performed for the USPSTF 3,27 identified no published studies that provided results of calibration for the US version of FRAX in the US population.…”
Section: Discussionmentioning
confidence: 99%
“…FRAX improves fracture prediction over the BMD measurement alone, however, the FRAX performance of predicting fracture risk varies in different study populations. Hence, there is room for further improvement in fracture prediction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, o custo de tratamento dessas fraturas para o sistema da saúde é elevado, visto que a chance de complicações é considerável e, em alguns casos, se faz necessário internação e tratamento cirúrgico. 4,5 Além da osteoporose, mais recentemente, a sarcopenia tem sido correlacionada ao aumento da probabilidade de um indivíduo vir a sofrer uma fratura por fragilidade. 6 A sarcopenia é definida por uma diminuição da massa muscular, levando à diminuição da capacidade de desempenho das atividades diárias e aumento na probabilidade de desfechos desfavoráveis como quedas, fraturas e morte.…”
Section: Introductionunclassified